A study on epidemiology, demographic and clinical presentation of acute encephalitis syndrome in children admitted to a tertiary care hospital in Central Gujarat - Shah, Rinki H.; Dangar, Riddhi (International Journal of Contemporary Pediatrics, 2026)
Background: Acute Encephalitis Syndrome is a major public health problem in major parts of the world especially in South and South East Asia. Globally, viral infections remain the most common cause of encephalitis in children. Present study was done to identify epidemiology, demographic and clinical presentation of Acute Encephalitis Syndrome in Children. Methods: This was tertiary care hospital based retrospective study. Data were collected form case record forms from month of July 2024 till December 2024. 57 patients fulfilling the criteria of AES in the age group of 1-12 years were enrolled in the study. Detailed history and investigations were sent including molecular testing of viral titre. Results: Total 57 children were enrolled. Mean age of presentation was 3.8 years. Majority of cases occur were seen in children less than 6 years of age. Slight male predominance (30 males=52.6% and 27 female 47.4%) was observed. Most patients were referred from rural area. Case fatality rate was observed to be 54.39%. 22 children were discharged while 4 patients went LAMA. CHPV was detected in 7 patients (12.28%) and Japanese encephalitis in one patient (1.75%). Fever was the major presenting complaint (85.96%) while vomiting was presenting complaints in 36 patients (63.16%). Altered sensorium was present in 23 patients (40.35%). Conclusions: AES remains a life-threatening neurological emergency in children. Young age, rural residence and severe clinical presentation contribute to poor outcome. Strengthening surveillance, early diagnosis and critical care management are essential to reduce mortality and long-term neurological sequelae.